PEMBENTUKAN PORTOFOLIO OPTIMAL PADA INDEKS SAHAM SYARIAH TERBARU DI PASAR MODAL INDONESIA - IDX SHARIA GROWTH (IDXSHAGROW) - Himmatul Mursyidah; Syarif Abdullah; Sri Istiyarti Uswatun Chasanah; Miftahul Huda; Fajri Ikhsan; Sidik Susilo (Math Program, Math and Science faculty, Pamulang University, 2023)
Seeing the needs of capital market industry players, the Indonesia Stock Exchange (IDX) developed an Islamic stock index. The newest type of sharia stock index launched by the IDX is IDX Sharia Growth (IDXSHAGROW). Stock investment requires a strategy to obtain maximum returns with minimal risk, one of which is diversification in portfolio formation. This study aims to form an optimal portfolio on the latest Islamic stock index on the Indonesian capital market, namely IDX Sharia Growth (IDXSHAGROW). The model used is the single index diversification model. The data used is for the period December 1, 2021 to. November 30, 2022 with weekly frequency. The results showed that the 30 shares that are members of IDXSHAGROW have 14 candidate shares. Furthermore, by making a cut-off, 11 stocks were included in the optimal portfolio with each proportion, namely MAPI 25.67%, KLBF 22.04%, AKRA 13.28%, UNTR 12.16%, MPMX 8, 3%, BRMS 4.4%, INCO 3.6%, LPPF 2.93%, ELSA 2.59%, AGII 2.54% and MYOR 2.48%. The optimal portfolio expected return value is 0.0017568 with a variance value of 0.00245 and a standard deviation of 0.04954 at weekly frequency. From the analysis of optimal portfolio formation in this study, the results were quite profitable for investors. This can be seen from the expected return value of the portfolio which is higher than the market value with each risk.